Reassessing Spanish chronicle writing before 900: the tradition of compilation in Oviedo at the end of the ninth century - Furtado, Rodrigo (2018)
This paper is a contribution to the origins of Spanish medieval historiography. I analyze two collections: the collection copied in the ‘Soriensis’ manuscript, most probably lost in a fire in 1671, and the so-called Chronica Albeldensis. I defend that shortly before the year 900 in Oviedo, Spain, where both these collections derive from, there was an interest in an easily readable kind of ‘universal history’ based on compilations of previous texts. These compilations were still modelled upon Eusebius/Jerome’s Chronicon, but they already supposed a great freedom in the handling of those previous texts, revealing great difficulty in understanding history as synchronic. They also formed an authentic historical canon subject to continuous additions and redesigns, becoming the backbone of Medieval Spanish compilatory historiography until at least the thirteenth century.